Property - Martin, Valerie (London ABACUS, 2009)
'Property' is an intricately told tale of both individual stories and of a country in a time of change, where ownership is at once everything and nothing, and where belonging, by contrast, is all.
Keywords: Louisiana -- Plantation life -- Slave insurrections